Lemon Crude Extract Modulates Ito Cells Activation in High Cholesterol Diet-Induced Liver Steatosis in Male Mice - Liqaa Oday Ali1, Ahmed G. AL-Helal1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Different types of polyphenols exist in many sources such as fruits, vegetables and herbs. For example, lemon has mainly flavonoids (such as Hesperidine, Eryoketrine, Narignine, Hesperidine, routine and chlorogenic acid). Research conducted in vivo and in vitro showed that lemons have different health benefits, such as anti-cancer effect, antimicrobial, antihyperlidemia and protective effect against liver disease. In addition, lemons are used to treat liver disorders. Therefore, current research was aimed to investigate the protective effect of the prolonged use of Lemon Crude Extract. Methods: Sixty male albino mice (4 weeks old, weighing between 20-25g) were used. They were divided into 3 groups (n= 20) for each group during the period from January 2018 to May 2018. Group I was used as control, Group II induction group was fed with (HCD), Group III was fed a (HCD) and treated with 1:1m/v of 100% (LCE) for 12 weeks.: Results Histological variations were identified in Group II by disturbed hepatic architecture, congestion in blood sinusoids and portal veins and infiltration of lymphocytes. Also, there was peri portal steatosis that was observed in HCD-fed mice. In addition, there was significant increase in Ito cells that was identified by desmin antibody. Moreover, these variations were less noticeable in Group III. Conclusion: Lemon has a protective effect against activation of Ito cells in fatty liver